Designing Sports Player's Valuation Indices (Case Study: Volleyball Players) - Mohammad Mohammadpoori; Mahvash Noorbakhsh; Maysam Shafiee Roodposhti (Shahid Bahonar University of Kerman, 2023)
The purpose of the present article is to design indicators and variables that represent the value of volleyball players. This research method is applied, which was done in a quantitative and qualitative way. The research tool was a semi-structured interview with experts in the field of player valuation. In this research, the statistical population included all the experts and specialists in human resources and financial management issues in sports, and also volleyball experts. The sample size included a number of volleyball sports experts who expressed their ideas to determine the variables. A total of 60 variables were extracted, of which 40 are quantitative indicators and 20 are qualitative indicators. These indicators are not only effective in the selection of players, but can also determine the price and final value of the players.